Assessment of postoperative cosmetic outcomes of distal form hypospadias repair with the Hypospadias Objective Scoring Evaluation (HOSE)Assessment of postoperative cosmetic outcomes of distal form hypospadias repair with the Hypospadias Objective Scoring - Asmir Jonuzi; Zlatan Zvizdić; Emir Milišić; Benjamin Kulovac; Amira Mešić; Semir Vranić (Medicinski glasnik, 2022)
Aim: A standardized assessment for the optimal repair of hypospadias remains elusive. The aim of this study was to assess a postoperative cosmetic outcome of hypospadias repair using a validated questionnaire, Hypospadias Objective: Scoring Evaluation (HOSE). Methods: During the period between January 2016 and May 2019, 40 patients who underwent hypospadias repair were identified and they agreed to a follow-up using the HOSE. Distal hypospadias repairs underwent a cross-sectional assessment of the cosmetic outcome. Cosmetic assessment was performed by an independent physician using the HOSE scoring system. Results: The native meatus was coronal in 10 (25%), subcoronal in eight (20%), and distal penile in 22 (55%) patients. Mean followup was 35.90 months (SD ±29.58) postoperatively (range 12-162 months). Complications occurred in one (2.5%) patient. Out of 40 uncomplicated repairs, 39 (97.5%) were satisfactory. A vertical slit-like meatus located at the distal glans was created in 33 (82.5%) boys, and at the proximal glans in seven (17.5%). The urinary stream was single and straight in 39 and spray in one patient. A straight erection was observed in 39 (97.5%) boys. The median HOSE score was 16 (range 12-16). One patient had a small, single coronal fistula. The technique used included tubularised incised plate urethroplasty. Conclusion: The HOSE score is simple, easy, non-invasive and non-expensive tool for objective assessment of long-term outcomes of hypospadias repair.
Keywords: hypospadias; tubularised incised plate; urethra; urethroplasty